Indicators of the relative availability of healthy versus unhealthy foods in supermarkets: a validation study - Stefanie Vandevijvere; Tara Mackenzie; Cliona Ni Mhurchu (BMC, 2017)
Abstract Background In-store availability of healthy and unhealthy foods may influence consumer purchases. Methods used to measure food availability, however, vary widely. A simple, valid, and reliable indicator to collect comparable data on in-store food availability is needed. Methods Cumulative linear shelf length of and variety within 22 healthy and 28 unhealthy food groups, determined based on a comparison of three nutrient profiling systems, were measured in 15 New Zealand supermarkets. Inter-rater reliability was tested in one supermarket by a second researcher. The construct validity of five simple indicators of relative availability of healthy versus unhealthy foods was assessed against this 'gold standard'. Results Cumulative linear shelf length was a more sensitive and feasible measure of food availability than variety. Four out of five shelf length ratio indicators were significantly associated with the gold standard (ρ = 0.70-0.75). Based on a non-significant difference from the 'gold standard' (d = 0.053 ± 0.040) and feasibility, the ratio of cumulative linear shelf length of fresh and frozen fruits and vegetables versus soft and energy drinks, crisps and snacks, sweet biscuits and confectionery performed best for use in New Zealand supermarkets. Conclusions Four out of the five shelf length ratio indicators of the relative availability of healthy versus unhealthy foods in-store tested could be used for future research and monitoring, but additional validation studies in other settings and countries are recommended. Consistent use of those shelf length ratio indicators could enhance comparability of supermarket food availability between studies, and help inform policies to create healthy consumer food retail environments.